Graphene-based nitrogen self-doped hierarchical porous carbon aerogels derived from chitosan for high performance supercapacitors. (July 2015) - Hao, Pin; Zhao, Zhenhuan; Leng, Yanhua; Tian, Jian; Sang, Yuanhua; Boughton, Robert I.; Wong, C.P.; Liu, Hong; Yang, Bin
Abstract: Graphene-based nitrogen self-doped hierarchical porous carbon aerogels were synthesized for supercapacitor electrode application by using chitosan as a raw material through a carefully controlled aerogel formation–carbonization–activation process. The as-synthesized N-doped graphene-based carbon aerogels contained both macropores and mesopores from the aerogel preparation and carbonization process, and micropores from the chemical activation, confirmed by TEM, SEM, BET, etc. Because chitosan is a nitrogen-containing renewable biopolymer, the carbon aerogel derived from chitosan in this work was N-self-doped. The carbonized carbon aerogel was composed of a graphene framework and amorphous carbon, and the ratio between these two components was controlled by the activation temperature. With an increase in activation temperature, the amorphous carbon was etched away gradually, and a stable graphene portion remained to form a framework. Accordingly, the performance of the graphene-based carbon aerogel as a supercapacitor varied with increasing activation temperature. Electrochemical investigation measurements showed that the N-doped graphene-based hierarchical porous carbon aerogel represents a good electrode candidate for construction of a solid symmetric supercapacitor, which displays a high specific capacitance of about 197 F g −1 at a current density of 0.2 A g −1 . In addition, the solid state supercapacitor displayed excellent cyclability with a capacitance retention of about 92.1% over 10, 000 cycles. The excellent energy storage ability of the chitosan-derived hierarchical graphene-based carbon aerogels is ascribed to the high conductivity of the graphene framework with nitrogen doping and the high storage ability of amorphous carbon with variable pore size and distribution. Graphical abstract: A facile and simple method to prepare the graphene-based nitrogen self-doped hierarchical porous carbon aerogels by using chitosan is proposed. Further the prepared hierarchical porous carbon aerogels were utilized as high performance supercapacitor electrodes which demonstrated an excellent capacitance retention ( 92.1%) over 10000 cycles. The excellent energy storage ability of the chitosan-derived hierarchical graphene-based carbon aerogels is ascribed to the high conductivity of the graphene framework with nitrogen doping and the high storage ability of amorphous carbon with variable pore size and distribution. Highlights: Graphene-based nitrogen self-doped hierarchical porous carbon aerogels were prepared by using renewable biopolymer chitosan as a raw material. A formation mechanism of graphene-based carbon aerogels is proposed. The carbonized carbon aerogel was composed of a graphene framework and amorphous carbon, and the ratio between these two components was controlled by the activation temperature. The performance of the graphene-based carbon aerogel as a supercapacitor varied with increasing activation temperature.